Adaptive Cycles [detail]. - Oh, Anela. (Tufts Archival Research Center, 2019)
Installation view from Liminal Space: 2019 SMFA Senior Thesis Exhibition. Thesis project statement: Nature is one of our greatest teachers: in creation, destruction, renewal, and balance. Humanity has found ways to disrupt nature and impose ourselves on the landscapes that shape our experience of life. As humans trying to understand our relationship with nature, we have created harm and destruction to the land directly. This destructive tendency carries over to how we experience natural settings. Out of these interactions, nature in America has become deeply tied to national identity and an individual sense of belonging; and the "other" that is people of color is alienated. Spaces that should be healing, a reminder that we are part of something greater, are instead unsettling and even dangerous to many who are "other" in American society.